KEMAMPUAN BERPIKIR KREATIF DALAM MATERI LUAS BANGUN DATAR DIKAJI DARI GAYA BELAJAR DI SMP - Dinda Dwi Larasati; Sugiatno Sugiatno; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to describe how the students' mathematical creative thinking abilities in the two-dimensional figure area material are studied from the learning styles of students in junior high schools. The aspects that are wanted to be clarified, namely: students' mathematical creative thinking abilities are studied from visual, auditory and kinesthetic learning styles. The research method used is descriptive method in the form of survey research. The subjects of the study were class VIII E students of SMP Negeri 02 Pontianak. Based on the results obtained indicate that the mathematical creative thinking ability of students with visual learning styles in class VIII of SMP Negeri 02 Pontianak, some students are able to achieve fluency and novelty indicators and others are only able to achieve fluency indicators, students' mathematical creative thinking ability with auditory learning styles in class VIII SMP Negeri 02 Pontianak able to achieve fluency and novelty indicators, and students' mathematical creative thinking ability with kinesthetic learning styles in class VIII SMP Negeri 02 Pontianak some students are able to reach fluency and novelty indicators and others are only able to reach fluency indicators.Keywords: Learning Styles, Mathematical Creative Thinking Abilities.